Consistent Routing and Scheduling with Simultaneous Pickups and Deliveries. Issue 8 (7th June 2020) - Emadikhiav, Mohsen; Bergman, David; Day, Robert
Abstract : We study the planning and scheduling of order shipments among laboratories of an instrument‐calibration company. To address a generic version of the company's combined routing and scheduling problem, we introduce a model variant with simultaneous pickups and deliveries in which consistency of site visits is also desired. We provide alternative formulations of the problem and propose branch‐and‐check and branch‐and‐price implementations, with an analysis of the instance characteristics for which each of these algorithms outperforms the other. Using the data collected from the company, our results indicate that the proposed framework can help the company to significantly reduce transportation costs and shipment times. We also investigate the influence of consistency and tardiness bounds on transportation costs, showing that while tardiness bounds significantly increase transportation costs, the enforcement of consistency requirements results in more consistent solutions at only slightly higher cost. The impact of enforcing consistency requirements increases when tighter tardiness bounds are imposed.